Mengendalikan Panic Attack dengan Meningkatkan Motivasi Belajar Selama Study From Home - Dwi Despiana; Deviana Rahma Putri; Ananda Irza Mahirah; Ananda Mahardika Salsabilla; Annisa Maharani Abidin; Desi Fitriani; Herju Liandri; Nurlia Putri; Rhanika; Ridaya; Siska Putri Wulansari; Tria Andaiyani (Jurnal Aksi Dosen dan Mahasiswa, 2023)
This research aims to determine the influence of learning motivation on student procrastination in Indonesia. The hypothesis proposed is that there is an influence of learning motivation on procrastination among students in Indonesia. The subjects were 124 students spread across Indonesia. The measurement tool uses a learning motivation and procrastination scale. By testing the normality of the research data, the results for the learning motivation variable were 0.200 (p > 0.05) and the procrastination variable was 0.200 (p > 0.05), this states that the data for these two variables had a normal distribution. The linearity test results obtained an F value of 7500.041 and a significant value (p) of 0.000 (p < 0.05). Based on the results of the Pearson's product correlation test, the significant value of learning motivation was 0.00 (p < 0.05) and the significant value of procrastination was 0.00 (p < 0.005). This shows that there is a relationship between learning motivation and procrastination.